Bye-bye muscle biopsy, we have autoantibodies with us now - Victoria Riddell; Sarah L Tansley (Indian Journal of Rheumatology)
Muscle biopsy is generally considered the gold standard diagnostic tool for patients with presenting with features suggestive of idiopathic inflammatory myopathy. Muscle biopsy is however an invasive test, the histopathological findings can be influenced by previous treatment and not all patients with myositis spectrum disease have muscle involvement. Myositis specific and associated autoantibodies can now be identified in the majority of patients with myositis. When present they identify homogeneous patient subgroups and have the potential to be key tools in developing a personalised approach to disease management. Here we review the utility of myositis specific and associated autoantibodies as diagnostic and prognostic tools.